Intravenous Mycobacterium Bovis Bacillus Calmette-Guérin Ameliorates Nonalcoholic Fatty Liver Disease in Obese, Diabetic ob/ob Mice - Inafuku, Masashi (PLoS One, 2015)
Inflammation and immune response profoundly influence metabolic syndrome and fatty acid metabolism. To analyze influence of systemic inflammatory response to metabolic syndrome, we inoculated an attenuated vaccine strain of Mycobacterium bovis Bacillus Calmette–Guérin (BCG) into leptin-deficient ob/ob mice. BCG administration significantly decreased epididymal white adipose tissue weight, serum insulin levels, and a homeostasis model assessment of insulin resistance. Serum high molecular weight (HMW) adiponectin level and HMW/total adiponectin ratio of the BCG treated mice were significantly higher than those of control mice. Hepatic triglyceride accumulation and macrovesicular steatosis were markedly alleviated, and the enzymatic activities and mRNA levels of lipogenic-related genes in liver were significantly decreased in the BCG injected mice. We also exposed human hepatocellular carcinoma HepG2 cells to high levels of palmitate, which enhanced endoplasmic reticulum stress-related gene expression and impaired insulin-stimulated Akt phosphorylation (Ser473). BCG treatment ameliorated both of these detrimental events. The present study therefore suggested that BCG administration suppressed development of nonalcoholic fatty liver disease, at least partly, by alleviating fatty acid-induced insulin resistance in the liver.